Acute motor axonal neuropathy in Ecuador: a retrospective case series with electrophysiological and functional correlation - Pérez León, Ana Karina; Salazar Lozano, Hugo Esteban; Pérez León, María Daniela; Pérez León, Andrea Carolina; Atapuma Madrid, Diego Fernando (Arandu UTIC, 2025)
Acute Motor Axonal Neuropathy (AMAN) is a severe Guillain–Barré Syndrome (GBS) variant characterized by acute flaccid paralysis and pure motor axonal involvement. In Latin America, its diagnosis remains challenging due to limited access to neurophysiological tools. This case series describes three Ecuadorian male patients diagnosed with AMAN between 2017 and 2025, each with recent gastrointestinal infection. Electromyography confirmed axonal motor neuropathy in all cases. One patient, a high-performance cyclist, required mechanical ventilation and fully recovered after IVIG. Another, a retired officer, showed partial improvement and remains orthotic-dependent. The third, a former conscript, developed irreversible quadriplegia despite treatment and prolonged ICU stay. Antiganglioside antibodies were tested in one case, revealing GD1a, GD1b, and GT1b positivity. These cases demonstrate the clinical heterogeneity of AMAN and the importance of early diagnosis, timely immunotherapy, and structured rehabilitation. Increased awareness and improved diagnostic capacity are essential to optimize outcomes in AMAN patients in resource-limited settings.